Pengaruh Pengaruh Model Game Based Learning Berbantuan Media Nearpod terhadap Penguasaan Konsep Hidrokarbon - Alfia Nur Fadhila; Evi Sapinatul Bahriah; Dedi Irwandi (Entalpi Pendidikan Kimia, 2026)
This study aims to determine the effect of the game-based learning model assisted by Nearpod media on student learning outcomes in hydrocarbon material in class XII. The method used is a quasi experimental with a nonequivalent control group design. Sampling used a purposive sampling technique with a population of 72 students consisting of 36 students of class XII IPA 1 (control class) and 36 students of class XII IPA 2 (experimental class). The research instrument was a multiple-choice test of 20 questions that had been tested for validation and reliability. Data were analyzed using parametric statistical techniques. The results of the posttest data hypothesis test using the t-test (Paired Sample Test) with a significance level of 5% obtained a value of .Sig (2-tailed) of 0.001 <0.05 so that H0 was rejected and H1 was accepted. The results of the analysis showed that the use of the game-based learning model assisted by nearpod had a significant effect on students' mastery of concepts in hydrocarbon material.